The Role of Sabhara Patrol in Suppressing the Crime of Motor Vehicle Theft - Febriana, Dwi Rizki (Police Studies Review, 2024)
The background of the problem that occurred was due to Sabhara patrol Unit activities in Cirebon City Police who had carried out their duties every day, but motor vehicle theft still often occurred. Therefore, a research was conducted aimed at describing the description of motor vehicle theft and analyzing the implementation of Sabhara patrols Unit in suppressing motor vehicle theft and identifying the factors that influence the implementation of patrols. Theories and concepts that used by author to answer the problem are routine activity theory, management theory and role theory. Meanwhile, the concept that used are Perkabaharkam No. 1 of 2017 concerning Patrol, the Sabhara Concept and the Patrol Concept. This research was conducted with a qualitative approach and using descriptive analysis research type. The focus of the research is the role of the Sabhara patrol in suppressing the theft of motorized vehicles in the Cirebon City area. The data used are primary data and secondary data. Data collection techniques with the stages interviews, observations, and document studies. Data validation uses data triangulation of sources, techniques, data and theories. While the analysis technique is the data reduction, data present, and making conclusion. Based on the results of research that motor vehicle theft is increasing every year. Meanwhile, the implementation of SatSabhara patrols in suppressing the number of patrols is still not optimal. This happen because the Satsabhara patrol method only uses four-wheeled patrol which is still applied today. Meanwhile, two-wheeled patrol is only done in incidental situations. In the implementation of patrols, the area of Cirebon City must be reviewed up to the remote areas but the constraints of the patrol personnel are limited. Factors affecting the implementation of the Sabhara patrol in the factor of facilities and infrastructure, the number of personnel and the method of implementing the patrol used. Based on the results of the study, the authors suggest to improve the management system at the Sabhara Unit, increase the intensity of patrols especially at night, establish coordination with the community and carry out patrol administration tasks in accordance with Perkabaharkam No.1 Tahun 2017.